Mechanical fractionation of tissues using microsecond-long HIFU pulses on a clinical MR-HIFU system. (17th November 2018) - Eranki, Avinash; Farr, Navid; Partanen, Ari; Sharma, Karun V.; Rossi, Christopher T.; Rosenberg, Avi Z.; Kim, AeRang; Oetgen, Matthew; Celik, Haydar; Woods, David; Yarmolenko, Pavel S.; Kim, Peter C.W.; et al.
Abstract: Purpose: High intensity focussed ultrasound (HIFU) can non-invasively treat tumours with minimal or no damage to intervening tissues. While continuous-wave HIFU thermally ablates target tissue, the effect of hundreds of microsecond-long pulsed sonications is examined in this work. The objective of this study was to characterise sonication parameter-dependent thermomechanical bioeffects to provide the foundation for future preclinical studies and facilitate clinical translation. Methods and materials: Acoustic power, number of cycles/pulse, sonication time and pulse repetition frequency (PRF) were varied on a clinical magnetic resonance imaging (MRI)-guided HIFU (MR-HIFU) system. Ex vivo porcine liver, kidney and cardiac muscle tissue samples were sonicated (3 × 3 grid pattern, 1 mm spacing). Temperature, thermal dose and T2 relaxation times were quantified using MRI. Lesions were histologically analysed using H&E and vimentin stains for lesion structure and viability. Results: Thermomechanical HIFU bioeffects produced distinct types of fractionated tissue lesions: solid/thermal, paste-like and vacuolated. Sonications at 20 or 60 Hz PRF generated substantial tissue damage beyond the focal region, with reduced viability on vimentin staining, whereas H&E staining indicated intact tissue. Same sonication parameters produced dissimilar lesions in different tissue types, while significant differences in temperature, thermal dose and T2 were observed between the parameter sets. Conclusion: Clinical MR-HIFU system was utilised to generate distinct types of lesions and to produce targeted thermomechanical bioeffects in ex vivo tissues. The results guide HIFU research on thermomechanical tissue bioeffects, inform future studies and advice sonication parameter selection for direct tumour ablation or immunomodulation using a clinical MR-HIFU system.